Implementasi Sistem Informasi Pembayaran Qris Berbasis Web Menggunakan Metode Prototype (Studi Kasus : SRC Toserba Mira) - Eliadi Zalukhu; Indra Yustiana; Imam Sanjaya (Jurnal Sains Informatika Terapan, 2026)
Advances in digital technology are driving the shift from cash to cashless transactions using the Quick Response Code Indonesian Standard (QRIS). An operational challenge at SRC Toserba Mira is the use of static QRIS codes that have not been systematically integrated with the store’s record-keeping system, resulting in transaction summaries and sales reports still being prepared manually and being prone to calculation errors. This study aims to design and implement a prototype of an integrated web-based QRIS payment information system to automate sales recording and reporting. The development method used is the prototype method. The system was built using MVC architecture with the Laravel framework, the PHP programming language, and a MySQL database. Testing was conducted through Black Box Testing, Security Testing, Performance Testing, and the System Usability Scale (SUS). The results of Black Box Testing showed that all major functional features including product management, QRIS payload integration, and report visualization functioned as expected. Security testing confirmed the system’s security, while performance testing demonstrated stable responsiveness in the hosting environment. Evaluation using the SUS yielded an average score of 77.91 (Acceptable category, Grade B/Good). The implementation of this system has successfully reduced manual operational steps, improved data recording accuracy, and provided transaction transparency for store owners and customers.